COMPARATIVE ANALYSIS TO PREDICT READING LITERACY BASED ON PISA 2022 USING GRADIENT BOOSTED DECISION TREES AND EXTREME GRADIENT BOOSTING - Hary Susanto; Ema Utami (G-Tech: Jurnal Teknologi Terapan, 2025)
Reading is a fundamental skill essential for interdisciplinary understanding and serves as a crucial indikator of a nation’s educational quality. PISA provides an international evaluation of students' reading literacy across various countries, including Indonesia. This study compares the performance of Gradient Boosting Decision Trees (GBDT) and Extreme Gradient Boosting (XGBoost), two widely recognized machine learning algorithms for predicting reading literacy, utilizing PISA 2022 data from 12.853 Indonesian students and 59 variables from the Student Questionnaire Data File. GBDT achieved R² of 0.5106, with optimal parameters (n_estimators = 150, learning_rate = 0.2, max_depth = 3, subsample = 0.9). XGBoost reached a higher R² of 0.5247, with parameters (n_estimators = 1000, learning_rate = 0.01, max_depth = 7, colsample_bytree = 0.3, min_child_weight = 20, gamma = 1, alpha = 0), indicating XGBoost's superior performance in predicting reading literacy. Further analysis revealed that the most significant variables in the GBDT model included students' access to technology at home, extracurricular creative activities, socioeconomic status, school involvement in sustainable development, and problem-solving skills. In contrast, significant variables in the XGBoost model included family support, socioeconomic status, school belongingness, family environment's effectiveness in fostering creativity, and student imagination.